Development of a four phase floating interleaved boost converter for photovoltaic systems - Lute, C.; Simões, M.; Brandão, D.; Al Durra, A.; Muyeen, S.M. (2014)
This paper explores the advantages of the Floating Interleaved Boost Converter, particularly with regards to solar photovoltaic power systems. This converter offers improved efficiency and voltage gain, while having lower input current ripple than other DC-DC boost converters. An analog linear feedback controller was developed, and adapted for discrete control. Two Maximum Power Point Tracking methods were explored, and their performances were evaluated in simulation. An experimental prototype was developed and demonstrated. The results show that this is a promising converter topology with many potential benefits for solar power applications.